Language Choice in Multilingual Speech Communities: A Sociolinguistic Study in the Wetland Area, Banjarmasin, South Kalimantan - Jumadi, Jumadi; Ahsani Taqwiem; Mu'in, Fatchul; Rusma Noortyani; Rina Listia; Rizky Amelia (UIN Salatiga, 2024)
The Banjar language is locally predominant in Banjarmasin City, whereas Indonesian is primarily used in educational and governmental settings. Research on language choice often centers on single-ethnicity groups, examining their use of mother tongues, national languages, or languages with colonial influence. This study, however, investigates the impact of cultural, social, and political factors on language choice within multiethnic communities – each with its own native language - across family, educational, and government domains. Using a mixed-methods approach with questionnaires and in-depth interviews, the study reveals the following findings: (a) Banjar speakers predominantly use the Banjar language at home and in public spaces but shift to Indonesian outside of the household, avoiding other regional language. (b) Members of the Dayak community favor either Banjar or Indonesian over their native language. (c) The Madurese, Bugis, and Minangkabau communities primarily use their native languages at home but prefer Indonesian or Banjar in public settings. (d) Javanese and Sundanese speakers use their native languages domestically but switch to Indonesian or Banjar in external interactions. In educational settings, (a) teachers predominantly use Indonesian for instruction and professional meetings, while (b) students use both Indonesian and Banjar. Within governmental contexts, sub-district employees use Indonesian in informal interactions with guests and Banjar in formal situations. These findings underscore important implications for fostering both local languages and Indonesian within educational and governmental framework.